Implementasi Pendekatan Direktif, Non Direktif dan Kolaboratif dalam Supervisi Pendidikan Islam (Studi Kasus di MAN Trenggalek) - Darsono, Darsono (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
Supervisors always improve their competence through either self-taught or continue studies S-2 or S-3 to be more professional in carrying out their duties as superintendent of education, namely from control to help teacher or schoolâs Headmaster. Supervisors in terms of supervision of the teachers need to understand the teachers prototype so that it can carry out supervision with the approach of the directive, non-directive and collaborative.Supervisors must have a strong personality in performing their duties so that teachers and principals respect him.